Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0226506
|View full text |Cite|
|
Sign up to set email alerts
|

Association between workplace bullying and burnout, professional quality of life, and turnover intention among clinical nurses

Abstract: Workplace bullying experienced by clinical nurses is associated with burnout, a factor that threatens the quality of nursing care and patient safety. This study examined the association of workplace bullying with burnout, professional quality of life, and turnover intention among clinical nurses. A descriptive cross-sectional study was conducted using a structured questionnaire. Data were collected from 324 nurses and were analyzed using t-test, one-way analysis of variance, and multiple regression. Controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
124
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(154 citation statements)
references
References 41 publications
22
124
1
7
Order By: Relevance
“…[ 26 , 27 ] Our result demonstrated that higher job satisfaction not only enhanced the level of compassion satisfaction, but also decreased a certain extent of burnout and secondary traumatic stress among psychiatric nurses, which is consistent with the findings of previous studies. [ 28 , 29 ] Moreover, job satisfaction is a good predictor of self-compassion, and self-compassion can ameliorate the level of burnout. [ 30 ] Therefore, targeting factors associated with job satisfaction may be important means of improving the poor ProQOL among psychiatric nurses in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 , 27 ] Our result demonstrated that higher job satisfaction not only enhanced the level of compassion satisfaction, but also decreased a certain extent of burnout and secondary traumatic stress among psychiatric nurses, which is consistent with the findings of previous studies. [ 28 , 29 ] Moreover, job satisfaction is a good predictor of self-compassion, and self-compassion can ameliorate the level of burnout. [ 30 ] Therefore, targeting factors associated with job satisfaction may be important means of improving the poor ProQOL among psychiatric nurses in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, emotional exhaustion reduces the commitment to the profession in the health sector (Jourdain, & Chênevert, 2010), leads to disengagement (Thanacoody, Newman & Fuchs, 2014) and low patient satisfaction (Gramstad et al, 2002;Argentero, Dell'Olivo & Ferretti, 2008). Moreover, it increases the intentions of health care workers to leave the job; in other words, it causes the idea of searching for other jobs (Kim et al, 2019). Therefore, health organisations should identify and implement practices that will reduce employee emotional exhaustion; it is particularly important to take the necessary precautions to minimise the emotional exhaustion, especially during this pandemic, where the emotional exhaustion level is high.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace bullying is an example of “unsafe” psychosocial work environment [ 19 ]. Studies showed that bullying leads to burnout [ 20 ], which adversely affects the physical and mental health of nurses [ 35 ]. These symptoms are prevalent in nursing, irrespective of gender, age, race, education levels, or work history [ 21 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%